UMP VC announces 8 commitments to sustain UMP excellence - Mimi Rabita, Abdul Wahit (2023)
PEKAN, 23 February 2023 - The Vice-Chancellor of Universiti Malaysia Pahang (UMP), Professor Dato’ Ts. Dr. Yuserrie Zainuddin announced eight commitments to sustain excellence in academic quality, research development and services so that UMP continues to be recognised internationally.